An exploration of the factors that have an influence on completion rates amongst secong year college based nursing students - Ramahlafi, Rose Malentsoe (My University, 2016)
PURPOSE The study explored the personal and social factors that have an influence on completion of training, in order to better understand the causes and suggest possible solutions for the high level of attrition among second year students. The study also sought to determine whether these factors have a different impact on successful and unsuccessful students. BACKGROUND The attrition rate of an average of 40% of nursing students in the Gauteng Nursing Colleges between the 2005 intake to 2008 is high, compared to 15%-20% that is found internationally. Anecdotal evidence shows that personal and social factors are an important reason for attrition and yet all efforts made thus far are to deal with academic issues. METHOD A qualitative exploratory and descriptive research design was used in one of the nursing colleges in the Gauteng Province. Purposive sampling was used from a population of 240 second year diploma students. The group consisted of both students who were thus far successful in their studies (meaning they had passed the first year at the first attempt), and those who had repeated a year of study. Forty nine participants wrote naïve sketches answering two questions:  What personal factors have influenced your academic progress?  What social factors have influenced your academic progress? A focus group interview was then conducted. Data was analysed using the Tech’s method of data analysis. FINDINGS The results confirmed that the causes of success or failure are multifactorial, and that there is no agreed way of classifying them internationally. The following themes emerged: study and work demands, educational programme challenges, individual student problems and student staff problems. It was confirmed that the personal and social factors play a role in completion or non- completion of studies, but that academic factors are inextricably intertwined with these personal and social factors. CONCLUSION The study found that the identified factors are prevalent in both the successful and unsuccessful students. However, the successful students appear to have intrinsic motivation, are able to come up with strategies to improve their academic performance, and are therefore able to succeed. The unsuccessful students are demotivated and find any challenges they encounter hurdles in making academic progress.
Submitted for the fulfilment of the requirements for the Degree MASTER OF SCIENCE ADVANCED NURSING EDUCATION In the Department of Nursing Education FACULTY OF HEALTH SCIENCES UNIVERSITY OF WITWATERSRAND AUGUST 2015